Hearing young children's perspectives: Reflections on research into left-behind children's lived experience in Chinese rural areas. Issue 2 (June 2023) - Liang, Kaixin; Niland, Amanda; Little, Cathy
Children's right to be heard is an issue raised in recent years in the Global North, which has also been acknowledged by Chinese researchers currently studying child development and education. However, Chinese researchers still often prefer the perspectives of adults in their research on young children, citing a lack of suitable methodologogy for collecting and interpreting young children's voices. This article recognises the significance of including young children's perspectives in research. It discusses how Western methodologies for listening to their perspectives, such as the Mosaic approach, can be adapted for use in Chinese socio-cultural contexts. By reflecting on the first author's research on the lived experience of leftbehind young children in a Chinese rural area, the article explores the development and implementation of such a methodology. The research findings indicate that the Mosaic approach, alongside phenomenological interviews and other research tools, provided an effective approach that enabled achievement of the research aims. Flexibility and reciprocity in relationships were two key contributors to effectiveness of this approach to research in a Chinese context.